The effect of self-management program with tele-nursing based on the Roper-Logan-Tierney model on self-care of hypertensive patients: a randomized controlled trial - Erden, Yasemin; Yildiz, Guzel Nur; Ciftci, Bahar; Avsar, Gulcin; Ozek, Suemeyra; Ozbek, Emrah; Sarialioglu, Arzu (Bmc, 2025)
ObjectiveTo examine the effect of tele-nursing and self-management programs based on the Roper-Logan-Tierney Model on the self-care of hypertension patients. Material and methodThe population of this randomized controlled interventional study consisted of hypertension patients who applied to the cardiology outpatient clinics of Van Regional Training and Research Hospital between September and December 2022. The sample consisted of 60 hypertensive patients over 18 who met the study criteria and agreed to participate. Data were collected with the Patient Information Form and Self-Care Management in Chronic Diseases Scale. Patients were randomized and divided into groups. Pre-test data for both groups were collected face-to-face. The intervention group received blood pressure measurement training with the Hypertension Education Booklet and self-management support with tele-nursing two times a week for 12 weeks. The control group did not receive any intervention. At the end of 6 weeks, interim tests were completed online, and after 12 weeks, post-tests were completed face-to-face. Data evaluation was performed with the blinding method. ResultsIt was determined that the differences between the mean scores of the intervention and control groups on the Self-Care Management Scale in Chronic Diseases midterm and posttest were statistically significant (p < 0.05). ConclusionIt was concluded that self-management support affects the self-care management of hypertension patients. Trial RegistrationThis research is a randomized controlled study. Therefore, a registration number was applied for at ClinicalTrials.gov. The registration number was obtained with the number NCT05316454. (First Posted 2022-04-07).
Keywords: Nursing; Hypertension; Self-management support; Tele-nursing; Self-care management